2016
DOI: 10.1016/j.ijproman.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Improving the estimation of probability of bidder participation in procurement auctions

Abstract: Anticipating the number and identity of bidders has significant influence in many theoretical results of the auction itself and bidders' bidding behaviour. This is because when a bidder knows in advance which specific bidders are likely competitors, this knowledge gives a company a head start when setting the bid price. However, despite these competitive implications, most previous studies have focused almost entirely on forecasting the number of bidders and only a few authors have dealt with the identity dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 38 publications
0
25
1
Order By: Relevance
“…Kreye et al (2013) found that the existence of competition can increase uncertainty perception at the competitive bidding stage because of the possibility of losing the PSS contract to a potential competitor. In contrast the research by Ballesteros-Pérez et al (2016) suggests that uncertainty perception may decrease because knowing the identity of possible competitors may make it easier to determine their possible pricing strategy. Yet, the specific effects of the existence of competition on uncertainty perception when bidding for PSS has thus far not been determined.…”
Section: Uncertainty Perception In Pricing Pssmentioning
confidence: 96%
See 2 more Smart Citations
“…Kreye et al (2013) found that the existence of competition can increase uncertainty perception at the competitive bidding stage because of the possibility of losing the PSS contract to a potential competitor. In contrast the research by Ballesteros-Pérez et al (2016) suggests that uncertainty perception may decrease because knowing the identity of possible competitors may make it easier to determine their possible pricing strategy. Yet, the specific effects of the existence of competition on uncertainty perception when bidding for PSS has thus far not been determined.…”
Section: Uncertainty Perception In Pricing Pssmentioning
confidence: 96%
“…Finally, the existence of competition can affect uncertainty perception on the competitive bidding stage for PSS (Ballesteros-Pérez et al 2016). Previous investigations have found contradicting insights on the potential effect of the uncertainty arising from competition.…”
Section: Uncertainty Perception In Pricing Pssmentioning
confidence: 99%
See 1 more Smart Citation
“…Such analysis may help to use e-RA in a more appropriate way, since they can be more successful when there is a higher level of competition on the supply market [28]. Therefore, estimates of the number of potential bidders competing in future tenders [29] should be of particular interest to buyers.…”
Section: Figure 1 Participation Of Suppliers In Tenders With and Withmentioning
confidence: 99%
“…For economics, they provide the basis for the development of equilibrium theories (to identify optimal auction arrangements for example Klemperer 2004), while for business, they offer the potential for a sharpened competitive edge through the analysis of competitor bidding behaviour (e.g. Ballesteros-Pérez, Skitmore, Pellicer, Gutiérrez-Bahamondes 2016, Ballesteros-Pérez, Skitmore, Pellicer, Zhang 2016.…”
Section: Introductionmentioning
confidence: 99%